Multiple-criteria Evaluation of Quality of Human Capital in the European Union Countries - Adam P. Balcerzak (Institute of Economic Research (IER), 2016)
Successful policies and programs leading to improvement of quality of human capital in the context of knowledge-based economy are currently considered as the basic condition for keeping global competitiveness of the European economy. It has been pointed as one of the most important aims of Europe 2020 strategy. In the EU all the countries are obliged to implement national strategies that should result in reaching that aims. As a result, it is necessary to compare countries' results, which can be useful for pointing the best practices and effective policy guidelines. Thus, the main aim of the article is to provide a multiple-criteria analysis of the quality of human capital in the EU countries at macroeconomic level. Special attention is given here to the results obtained by new member states of the EU. The research is done for the years 2001-2012. Additionally, it gives some insight on the possible influence of the global financial crisis on the dynamics of the quality of human capital in the EU countries. Data from Eurostat is used. Hellwig's method of taxonomic measure of development with the constant pattern (ideal solution) for the entire period is applied in the research. The Hellwig's method is very close to TOPSIS method, which is based on a concept of similarity to ideal solution and which is currently commonly applied in multiple-criteria decision-making (MCDM). After obtaining the relative measure for the quality of human capital, the countries were grouped into homogenous subsets with application of natural breaks method. The main advantages of the applied methods are high elasticity and methodological simplicity, which is crucial in the case of multiple-criteria decision analysis (MCDA).
Keywords: C38; E24; 330; multiple-criteria decision-making (MCDM); multiple-criteria decision analysis (MCDA); Hellwig's method; human capital; European Union